Psychological constructs measured by the MCMI-III and 16PF5 of subjective tinnitus sufferers : an exploratory quantitative study - Eskell-Blokland, Linda (University of Pretoria, 2017)
Mini Dissertation (MA)--University of Pretoria, 2017.